Stress-triggered signaling affecting survival or suicide of Streptococcus pneumoniae - Cortes, Paulo (2014)
Streptococcus pneumoniae is a major human pathogen that can survive to stress conditions, such as the acidic environment of inflammatory foci, and tolerates lethal pH through a mechanism known as the acid tolerance response. We previously described that S. pneumoniae activates acidic-stress induced lysis in response to acidified environments, favoring the release of cell wall compounds, DNA and virulence factors. Here, we demonstrate that F0F1-ATPase is involved in the response to acidic stress. Chemical inhibitors (DCCD, optochin) of this proton pump repressed the ATR induction, but caused an increased ASIL. Confirming these findings, mutants of the subunit c of this enzyme showed the same phenotypes as inhibitors. Importantly, we demonstrated that F0F1-ATPase and ATR are necessary for the intracellular survival of the pneumococcus in macrophages. Alternatively, a screening of two-component system (TCS) mutants showed that ATR and survival in pneumocytes were controlled in contrasting ways by ComDE and CiaRH, which had been involved in the ASIL mechanism. Briefly, CiaRH was essential for ATR (ComE represses activation) whereas ComE was necessary for ASIL (CiaRH protects against induction). They did not regulate F0F1-ATPase expression, but control LytA expression on the pneumococcal surface. These results suggest that both TCSs and F0F1-ATPase control a stress response and decide between a survival or a suicide mechanism by independent pathways, either in vitro or in pneumocyte cultures. This biological model contributes to the current knowledge about bacterial response under stress conditions in host tissues, where pathogens need to survive in order to establish infections.